2020
DOI: 10.1155/2020/4908189
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Class 1 Integron Gene Cassette Arrays Contribute to Antimicrobial Resistance of Diarrheagenic Escherichia coli

Abstract: Class 1 integrons (c1-integrons) are associated with multidrug resistance in diarrheagenic Escherichia coli (DEC). However, little is known about gene cassettes located within these c1-integrons, particularly truncated c1-integrons, in DEC strains. erefore, the aims of the present study were to reveal the relationship between antimicrobial resistance and the presence of truncated c1-integrons in DEC isolates derived from human stool samples in Japan. A total of 162 human stool-derived DEC isolates from Japan w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
5
4
1
Order By: Relevance
“…Overuse of antibiotics with and/or without prescription is responsible for emergence of multidrug resistance among clinical isolates, which is a serious public health issue and can create therapeutic difficulties for patients. The findings of this study show high levels of resistance to ampicillin, trimethoprim–sulfamethoxazole and tetracycline among STEC, which is in agreement with previous findings in Japan, China, South Africa, Iran, Mexico and Michigan [ 24 29 ]. Also relatively lower levels of resistance to cefotaxime, ceftazidime, ciprofloxacin and levofloxacin was revealed, a finding which was similar to those reported by others [ 30 , 31 ], and opposite to that reported by Zhang et al in china [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overuse of antibiotics with and/or without prescription is responsible for emergence of multidrug resistance among clinical isolates, which is a serious public health issue and can create therapeutic difficulties for patients. The findings of this study show high levels of resistance to ampicillin, trimethoprim–sulfamethoxazole and tetracycline among STEC, which is in agreement with previous findings in Japan, China, South Africa, Iran, Mexico and Michigan [ 24 29 ]. Also relatively lower levels of resistance to cefotaxime, ceftazidime, ciprofloxacin and levofloxacin was revealed, a finding which was similar to those reported by others [ 30 , 31 ], and opposite to that reported by Zhang et al in china [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar pattern was reported from India [ 30 ]. The prevalence of MDR was 60.9%, which was both lower [ 25 ] and higher [ 24 ] than results reported by others. Furthermore, almost all of the ESBL-producing STEC strains were MDR.…”
Section: Discussioncontrasting
confidence: 57%
“…is indicates that quinolone resistance genes are not cassette-born. is coincides with the study of Kubomura et al who found that except for dfrA and aadA genes, the antibiotic resistance genes are mostly found outside the integrons [69].…”
Section: Discussionsupporting
confidence: 91%
“…e reported cassettes encode for resistance to trimethoprim and aminoglycosides and have been recorded among class I integrons in previous studies [10,13,61,68,69]. e diversity of class I integron cassettes is comparable to previous studies [10,61] that reported 10 and 7 different gene cassettes among the tested isolates, respectively.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation